Estrategias de control de Mancha Foliar con fungicidas de protección y sistémicos en Lechuga (Lactuca sativa) en Lamas - Sandoval Cárdenas, Katty (2005)
The present test(essay) of " Control of spot to foliate with protection fungicidas and sistemicos in lettuce (Lactuca sativa) ", carried out with the aim(lens) tó evaluate strategies of chemical control for the spot to foliate caused by the mushroom Cercospora longíssima Cugina ex-Trav. Developed in the horticultural field called " I Found(Fuse) the Retum " of property of the lng. Jorge Peláez Rivera in the Sector Remoyacu, District and Province of Muds and Region St Martín, with Latitude South 6 " 20 ' 15", Length West 76 º 30 ' 45 ", Altitude 814 m. S. n. m., who was led under the design of block completely at random by 6 treatments and 4 repetitions. Ali the applications with fungicides reducieron the effect and severity of the disease cercosporiosis of the lettuce, being major with the treatment 4 (Rotation of fungicídes sistémico S2 more protectantes P1 and P2) with minor number of spotted leaves(sheets) and a yield of 14 348.18 Kg/ha of lettuce. The treatment 3 (protection fungicida P2), it{he ,she) obtained SPs major clear usefulness(utility). 2 444.93 new Suns with a relation I benefit cost of 1.53. The treatment witness registered major effect and severity of the disease, increasing with the growth and development of the plant(floor).